The Effect Of Education Using Video Media on Optimizing Toddler Nutrition on The Knowledge of Mothers of Toddlers - Safa Haya Faradila; Rr. Dewi Ngaisyah; Yelli Yani Rusyani (Saintify Publish, 2024)
Background: Data from the Ngemplak Community Health Center shows that 3.41% of toddlers are experiencing malnutrition, with toddlers experiencing malnutrition in Sindumartani sub-district in 6 posyandu in 2022. Objective: This research aims to determine the effectiveness of educational media about optimizing toddler nutrition on the knowledge of mothers of toddlers in the Ngemplak 1 Community Health Center Working Area, Yogyakarta City. Methode: This type of research is a quasi-experiment, the researcher examines the influence of two variables, namely providing nutritional education to mothers of toddlers on knowledge about optimizing toddler nutrition. The research provided treatment (intervention) on the subject, namely nutrition optimization education on the knowledge of mothers of toddlers with 62. Respondents knowledge wa meansured using t-test analysis a questionnaire in bivariate testing using the paired t-test statistical test α=0,05. Results: In this study, using t-test analysis based on the Paired Sample t-test, significance = 0.000 was obtained, less than the significance level (α) = 0.05. In tabet t, a negative t count is obtained, namely -19.119, which means the average before treatment is lower than the average after treatment. Conclusion: Education using video media is effective in increasing mothers' knowledge about optimizing toddler nutrition at the Ngemplak 1 Community Health Center, Sleman, Yogyakarta.